Individual differences in the engagement of habitual control over alcohol seeking predict the development of compulsive alcohol seeking and drinking. (6th May 2021) - Giuliano, Chiara; Puaud, Mickaël; Cardinal, Rudolf N.; Belin, David; Everitt, Barry J.
Abstract: Excessive drinking is an important behavioural characteristic of alcohol addiction, but not the only one. Individuals addicted to alcohol crave alcoholic beverages, spend time seeking alcohol despite negative consequences and eventually drink to intoxication. With prolonged use, control over alcohol seeking devolves to anterior dorsolateral striatum, dopamine‐dependent mechanisms implicated in habit learning and individuals in whom alcohol seeking relies more on these mechanisms are more likely to persist in seeking alcohol despite the risk of punishment. Here, we tested the hypothesis that the development of habitual alcohol seeking predicts the development of compulsive seeking and that, once developed, it is associated with compulsive alcohol drinking. Male alcohol‐preferring rats were pre‐exposed intermittently to a two‐bottle choice procedure and trained on a seeking–taking chained schedule of alcohol reinforcement until some individuals developed punishment‐resistant seeking behaviour. The associative basis of their seeking responses was probed with an outcome‐devaluation procedure, early or late in training. After seeking behaviour was well established, subjects that had developed greater resistance to outcome devaluation (were more habitual) were more likely to show punishment‐resistant (compulsive) alcohol seeking. These individuals also drank more alcohol, despite quinine adulteration, even though having similar alcohol preference and intake before and during instrumental training. They were also less sensitive to changes in the contingency between seeking responses and alcohol outcome, providing further evidence of recruitment of the habit system. We therefore provide direct behavioural evidence that compulsive alcohol seeking emerges alongside compulsive drinking in individuals who have preferentially engaged the habit system. Abstract : Individual differences in the development of insensitivity to devaluation of the seeking outcome predict the subsequent development of compulsive alcohol seeking. Once established, compulsive alcohol seeking is insensitive to degradation of the contingency between seeking and taking outcomes. The development of compulsive alcohol seeking is not preceded or predicted by a higher level of alcohol intake. However, once established, it is associated with an escalation of free alcohol intake and insensitivity to adulteration of alcohol with quinine.